Selective and direct immobilization of cysteinyl biomolecules by electrochemical cleavage of azo linkage - Jung, Hyun Joo (Langmuir : the ACS journal of surfaces and colloids, 2010)
Controlled orientation and reserved activity of biomolecules, when site-selectively immobilized in a highly integrated manner on a minimal time scale, are crucial in designing biosensors for the multiplex detection. Here, we describe a novel method for the orientation-controlled immobilization of biomolecules based on site-selective electrochemical activation of p-hydroxyazobenzene self-assembled monolayer (SAM) followed by one-step coupling of cysteinyl biomolecules. The p-aminophenol, a product of reductive cleavage of p-hydroxyazobenzene, was subsequently oxidized to yield p-quinoneimine which then conjugated with cysteinyl biomolecules through 1,4-Michael addition, thus obviating additional linker agents and the related time consumption. Using this method, we selectively activated the electrode surface and immobilized laminin peptide IKVAV, a neurite promoting motif. When we cultured hippocampal neurons on the electrode, the extended neurites were found only within the electrochemically activated area. Hence, the proposed method represents a new promising platform for the patterning of functional peptides, active proteins, and live cells